Factoriser les expression suivante avec l'aide des identitées:

A= x²+8x+16 B=9+4x²-12x C=x²-100 D=(2x-1)²-81 E=(3x-5)(2x-3)-(3x-()(5x+3)

A=x²-16 B=(7x-8)² -(3x-2)(7x-8) C=x²+10x+25 D=y²-18y+81 E=9x²+64+48x

A=(3x-4)(5x+2)-(3x-4)² B=9x²+30x+25 C=(4x-7)²-121 D=49y²-64 E=16x²+25-40x

A=(3x+4)²-49 B=25x²-36 C=4x²-8x+4 D=(5x-1)²-(x+3)² E=(4x²-12+9)-4

1

Réponses

Meilleure réponse !
2013-03-17T16:07:51+01:00

A= x²+8x+16= ( x +4 )²                       B=9+4x²-12x = ( 2x-3)²    C=x²-100 = ( x+10) ( x-10)

D=(2x-1)²-81=( 2x +8) (2x -10)         A= x²-16= ( x+4) (x-4)       B=(7x-8)² -(3x-2)(7x-8)  = (7x-8) (4x-6)

C=x²+10x+25 = (x +5)²                      D=y²-18y+81= (y -9)²        E=9x²+64+48x =(3x + 8)²                       A=(3x-4)(5x+2)-(3x-4)² = (3x -4) (2x +6)                                      B=9x²+30x+25 = (3x +5)²              C=(4x-7)²-121 = (4x -18) (4x +4)     D=49y²-64 = (7y -8) (7y +8)          E=16x²+25-40x = (4x + 5)²   A=(3x+4)²-49 = (3x -3) (3x +11)       B=25x²-36 = (5x -6) (5x +6)           C=4x²-8x+4 = (2x - 2)²

D=(5x-1)²-(x+3)² = (4x-4) ( 6x +2)